Research on Interactive Oscillation Suppression of Grid-forming VSC Grid-connected system - Wang, Yi; Wang, Chen; Li, Qionglin; Yang, Ziyi; Shan, Weiwei; Qin, Benshuang (Proceedings - International Conference on Harmonics and Quality of Power, 2024)
The "double high" background presents new demands for grid-connected inverters, namely grid-forming capability and inertia support capability. virtual synchronous generator (VSG) technology has rapidly developed to meet these demands. However, when there is a disturbance in the command power, interaction between VSG control loops can easily cause interactive oscillations, threatening the safe and stable operation of the new type system. Consequently, the improve the VSG is proposed to improve the dynamic response characteristics by using speed damping power high-pass feedback in active power-frequency control loop. Firstly, bode plots are applied to compare the transient and steady-state characteristics between traditional and improved VSG control methods. Secondly, the interaction of active power loops is analyzed using the relative gain array (RGA) principle. Finally, simulations are conducted to verify the proposed method for suppressing interactive oscillations, and which indicate that the improved method could well suppresses the interactive oscillation.